PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS 3D AURORA PRESENTATION PADA PEMBELAJARAN - Sisri Wahyuni; Dina Fitria Handayani (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
The purpose of this research is to develop a 3D aurora presentation based learning media. This type of research is R&D (development). Media development based on aurora 3D presentation using 4D models. The data technique uses interview, observation, and documentation techniques. Data analysis using qualitative and quantitative. The validation of this learning media is 3 validators (2 material validators and 1 media validator). The practicality of this learning media was carried out by 4 practical people (1 educator and 3 students). The effectiveness of this learning media was carried out by 3 students. The results of the research were in the form of aurora-based 3D teaching media product in the form of a slide presentation. The results of the validation: 1) the first material expert was 82% with a very valid category and the proportion of the second material expert was 80% in the valid category, 2) the validation result of the media expert was 92.5% with the very valid category. Results Educator Practicality 95.8% with very practical category. The results of the practicality of the first and second students, 91.6% with the very practical category, and the third students getting 93.7% with the very practical category. The average practical result of students was 92.3% with the very practical category. The results of the first students were 80% in the effective category, the second students were 90% in the very very effective category, and the third students were 75% in the effective category, on average, they had 80% of the effective category. This shows that the 3D aurora-based learning media theme presentation 8 of our friend's environment, sub-theme 2 changes to the learning environment 2 for grade V SD is very valid, practical and effective and is suitable for use as a medium in learning activities.Keywords: Media, Aurora 3D Presentation, Thematic.